2018
DOI: 10.1080/02770903.2018.1452034
|View full text |Cite
|
Sign up to set email alerts
|

“…I've said I wish I was dead, you'd be better off without me”: A systematic review of people's experiences of living with severe asthma

Abstract: This systematic review found a paucity of qualitative studies reporting on people's perspectives of living with severe asthma, and a focus on clinical rather than personal issues. Our synthesis reveals that severe asthma was disempowering, and a threat to identity and life roles. What was important to people living with severe asthma was striving to achieve a greater level of personal control over their condition, but these efforts received little support from their healthcare providers. Thus, more attention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
(104 reference statements)
3
41
1
Order By: Relevance
“…A systematic review of five qualitative studies describing the experience of living with severe asthma confirms these findings, and provides further insight as to why people with severe asthma have such quality of life burden, with four interrelated subthemes described 13 . In the theme “striving for autonomy through dealing with symptoms and treatment,” the burden of coping with symptoms is evident; while these relate to the continuous disease‐specific symptoms of wheeze, breathlessness and cough, participants also highlight the panic and fear that they experience in relation to the unpredictability of their next attack 13 …”
Section: Understanding the Patient's Perspectivementioning
confidence: 64%
See 3 more Smart Citations
“…A systematic review of five qualitative studies describing the experience of living with severe asthma confirms these findings, and provides further insight as to why people with severe asthma have such quality of life burden, with four interrelated subthemes described 13 . In the theme “striving for autonomy through dealing with symptoms and treatment,” the burden of coping with symptoms is evident; while these relate to the continuous disease‐specific symptoms of wheeze, breathlessness and cough, participants also highlight the panic and fear that they experience in relation to the unpredictability of their next attack 13 …”
Section: Understanding the Patient's Perspectivementioning
confidence: 64%
“…Qualitative studies give some insight into this behaviour in severe asthma and the impact of treatment on quality of life. The burden of treatment and the adverse effects of medication were noted as significant issues by participants in all of the studies 4 , 13 . Patients will frequently weigh up the costs and benefits of treatment in an attempt to lead a normal life.…”
Section: Understanding the Patient's Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In the context of a long‐term and debilitating condition such as severe asthma, even daily activities might present a threat to feelings of personal control, choice and decision making. A recent review identified few studies investigating patients’ perceptions of living with severe asthma; these studies focused on the clinical rather than personal aspects of the lived experience of severe asthma. The review highlighted that severe asthma can be disempowering and poses threats to identity and life roles …”
Section: Introductionmentioning
confidence: 99%